The acute effects of self-myofascial release (smr) using rolling bar on increasing musculoskeletal flexibility / Kalam Azad Isa … [et al.] - Isa, Kalam Azad; Wan Norman, Wan Mohd Norsyam; Ismail, Muhammad Aizudin; Ahmad Sidiki, Ahmad Firdaos Syauqi (Universiti Teknologi MARA Cawangan Pahang, 2020)
Flexibility is one of the six health-related components which is paramount in athlete’s performance by increasing the range of musculoskeletal movement. Additionally, prevention of musculoskeletal injury is highly associated with great flexibility during unimpeded sporting execution. Traditionally, techniques such as static, dynamic, ballistic and Proprioceptive Neuromuscular Facilitation stretching has proven being able to lengthen and increase the musculoskeletal flexibility. In recent studies, Self-Myofascial Release (SMR) technique is proclaimed to also increase person’s musculoskeletal flexibility by increasing the range of motion with the prolonged application. However, limited empirical evidence showed the onset application of SMR in increasing the musculoskeletal flexibility. Therefore, N=24 healthy adolescent aged 13.46(.509) was recruited purposely to test the acute effect of SMR on lower extremities flexibility by using a pre-post experimental design. This result of this study indicated that there is an acute effect of SMR application of musculoskeletal flexibility with t (23) = 7.402, p < 0.05. It is suggested for future study that a comparison between prolonged and onset application of SMR on the musculoskeletal range of motion is carried out and established